2011
DOI: 10.15288/jsad.2011.72.221
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive Periods for Adolescent Alcohol Use Initiation: Predicting the Lifetime Occurrence and Chronicity of Alcohol Problems in Adulthood

Abstract: ABSTRACT. Objective: This study examined the association between age at alcohol use onset and adult alcohol misuse and dependence by testing the sensitive-period hypothesis that early adolescence (11-14) is a vulnerable period of development during which initiating alcohol use is particularly harmful. Method: Data came from a longitudinal panel of 808 participants recruited in 1981. Participants were followed through age 33 in 2008 with 92% retention. Results: Onset of alcohol use before age 11 (late childhood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
97
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 134 publications
(104 citation statements)
references
References 36 publications
6
97
0
1
Order By: Relevance
“…Furthermore, as Donovan et al (2004) concluded in the proceedings of the 2003 symposium of the Research Society on Alcoholism, there is a dearth of studies focusing on alcohol use among elementary students, or the "really underage" drinkers. Importantly, using prospective, longitudinal data, Guttmannova et al (2011) found that very early onset of alcohol use (before age 11), when compared with initiation during early, mid-, and late adolescence, was related to an increased chronicity of alcohol dependence in young adulthood. Although these studies have documented the link between early alcohol use and adult alcohol use disorder, the mechanisms linking the two are not well understood.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Furthermore, as Donovan et al (2004) concluded in the proceedings of the 2003 symposium of the Research Society on Alcoholism, there is a dearth of studies focusing on alcohol use among elementary students, or the "really underage" drinkers. Importantly, using prospective, longitudinal data, Guttmannova et al (2011) found that very early onset of alcohol use (before age 11), when compared with initiation during early, mid-, and late adolescence, was related to an increased chronicity of alcohol dependence in young adulthood. Although these studies have documented the link between early alcohol use and adult alcohol use disorder, the mechanisms linking the two are not well understood.…”
mentioning
confidence: 98%
“…Using the same sample, the present study expands on the fi ndings of Guttmannova et al (2011) and examines potential factors that may account for the link between pre-adolescent onset of alcohol use and increased chronicity of alcohol dependence in adulthood. Specifi cally, this study examined the following three competing hypotheses: (1) a marker hypothesis, (2) a compromised adolescent functioning hypothesis, and (3) an increased substance use hypothesis.…”
mentioning
confidence: 99%
“…Rather than being a fatal weakness, the replication of those relations using a variety of terms suggests a robust association, which has been found in cross-sectional surveys [4][5][6], in some [7][8][9][10][11] but not all [12] longitudinal studies and studies that control for genetics [13], such as studies of identical twins [14].…”
Section: The Usefulness Of 'Age At First Drink' As a Concept In Alcohmentioning
confidence: 99%
“…126 Social-emotional development Meta-analytic findings involving previously institutionalized adopted infants document the latter half of the first year as a sensitive period for promoting attachment security. 113,127 Findings suggest that the early years of life are a particularly salient time period for preventative interventions to reduce negative emotionality and behavioral problems or promote self-regulation or pro-social behaviors 128,129 Adverse long-term consequences associated with exposure in childhood or adolescence to developmental risks such as: Societal violence; 149 ; Alcohol; 150 Culturally based socialization for aggressive behavior; 151 Positive consequences associated with exposure in childhood or adolescence to positive developmental influences such as: Social support, which facilitates children's resilience after occurrence of a major natural disaster; 152 Community acceptance, which supports the adjustment of former child soldiers; 153 Treatment programs for abused children; 154 Programs to increase child pro-social behavior and reduce aggression; 155 School based programs to promote better inhibitory control; 144 Drug prevention programs 156 Programs for reducing the impact of parental divorce on offspring. 157 Cognitive/academic competence.…”
Section: Child Outcomes: Early Exposures or Interventions (Infancy-eamentioning
confidence: 99%